Fantastic squeaks and where to find them: producing and analysing audible acoustics from leipäjuusto - Nurkkala, Elina (Walter de Gruyter GmbH, 2025)
Chewing not only converts food chunks to digestible proportions, it also conveys audible acoustics resulting in a perception on the type and condition of the food being eaten. As biomedical engineers, we may want to reproduce the same eating experience for those who cannot chew or for those who have allergic reactions to some foods. But to understand this psychoacoustic phenomenon better, it is crucial to understand what produces the sound of specific foods. The purpose of this paper is to present a straightforward methodology to produce audible acoustics from a notoriously loud Finnish delicacy and analyse the sound produced. One hundred samples of leipäjuusto and one hundred samples of Gouda cheese for controls were subjected to shear between a bamboo board and a wetted blade. All leipäjuusto samples and none of the Gouda cheese samples produced audible squeaks. A 0.1-s delay between blade displacement and sound production was observed. We attribute this delay to the buildup to release. The frequency spectra from pushing and pulling movements were observed to have only negligible differences. This indicated that the internal structure between events did not change. Therefore, the hypothesis that a disrup